Modelling and Forecasting Demand for Nepali Tourism - Paudyal, Shoora B. (NRB Economic Review, 2014)
In this paper international demand for Nepali tourism from the selected major markets has been estimated using time series data of number of tourist arrivals, per capita income, own price and prices of related goods. Autoregressive distributive lagged (ARDL) models are applied as a tool of estimation. This study confirms that tourism demand for Nepal is the composite function of disposable income, own price, cross price, lags of these variables, word of mouth of the visitors and qualitative factors captured by dummies. The most important policy implication can be derived from the words of mouth of the visitors. This manifests that only the good impression on the visitors can generates better words of mounth in favour of destination which underscores the up-gradation of the tourist products for the better image of the destination. The best performed models are used for forecasting the growth rates of tourist arrivals from the eight major markets for 2010 to 2020. The forecasted growth rates of tourist arrivals from major eight market are found very close to the actual average annual growth rates for 2006 to 2010.